POLITIK KEBIJAKAN PENDIDIKAN AGAMA DAN KEAGAMAAN: REVITALISASI UPAYA PEMERINTAH TERHADAP PENDIDIKAN KEAGAMAAN - Ahmad Syafii; Siti Qurrotul A’yuni (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
Indonesia is the biggest archipelago country in the world, the government has tried to prosper the people by issuing policies on regional autonomy. Regional autonomy in its development is widespread in all fields, one of them in education. Autonomy Education gained much support among the people, thus giving birth to Decentralization of Education, namely to give up government responsibility according to the needs and capabilities of each region. The effort has been regulated in Law Number 20 Year 2003 on National Education System supported by Government Regulation no. 55 of 2007. However, these efforts have not been fully realized, so that sometimes cause gap and prolonged criticism. Therefore we as a policy-bearer must prioritize the principle good governance in Decentralization of Education.